THE HEART IS PERPETUAL MOTION MACHINE - Fomina Mayde Anatolevna (Research Focus International Scientific Journal, 2024)
Our heart is often compared with a motor. Cardiac wall consists of three layers.The heart makes 2.5-3 billion beats in it`s life. It can contract for some time after death. Normal rate of heart contractions in an adult is 70 beats per minute, in newborns 120-140. Great progress has been made in cardiac surgery.